2020
DOI: 10.3390/jcm9030661
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Short-Form 12 Item Version 2 (SF−12v2) Health-Related Quality of Life Survey and Disutilities Associated with Relevant Conditions in the U.S. Older Adult Population

Abstract: This study aimed to validate the Short-Form 12-Item Survey—version 2 (SF−12v2) in an older (≥65 years old) US population as well as estimate disutilities associated with relevant conditions, using data from the Medical Expenditure Panel Survey longitudinal panel (2014–2015). The physical component summary (PCS) and mental component summary (MCS) scores were examined for reliability (internal consistency, test-retest), construct validity (convergent and discriminant, structural), and criterion validity (concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The Short form-12 items health survey (SF-12) (38) is one of the most commonly used health-related quality of life (HRQoL) questionnaires, and it has become widely used in community-based health surveys and physical and mental illness outcome assessments due to its brevity and psychometric performance (39,40). A recent study (41) showed that PCS and MCS demonstrated high internal consistency (Cronbach's α-PCS: 0.87, MCS: 0.86) and good and moderate test-retest validity, respectively (intraclass correlation coefficient: PCS: 0.79, MCS: 0.59). A previous study (42) reported acceptable to good levels of reliability for PCS internal consistency coefficient (ICC) (Cronbach's α = 0.78) and MCS ICC (Cronbach's α = 0.60).…”
Section: Short Form-12 Items Health Survey (Sf-12)mentioning
confidence: 99%
“…The Short form-12 items health survey (SF-12) (38) is one of the most commonly used health-related quality of life (HRQoL) questionnaires, and it has become widely used in community-based health surveys and physical and mental illness outcome assessments due to its brevity and psychometric performance (39,40). A recent study (41) showed that PCS and MCS demonstrated high internal consistency (Cronbach's α-PCS: 0.87, MCS: 0.86) and good and moderate test-retest validity, respectively (intraclass correlation coefficient: PCS: 0.79, MCS: 0.59). A previous study (42) reported acceptable to good levels of reliability for PCS internal consistency coefficient (ICC) (Cronbach's α = 0.78) and MCS ICC (Cronbach's α = 0.60).…”
Section: Short Form-12 Items Health Survey (Sf-12)mentioning
confidence: 99%
“…Health preference for CHOP-related AEs was infrequently reported. The disutility for CHOP-related FN was significant (−0.15) and aligned with the impact of functional limitations on HRQoL in older adults 51 . CIA-related fatigue, as measured by FACT-An, indicated substantial functional impairment and reduced patient QoL.…”
Section: Discussionmentioning
confidence: 71%
“…Health preference for CHOP-related AEs were infrequently reported. The disutility for CHOP-related FN was significant (-0.15) and aligned with the impact of functional limitations on HRQoL in older adults [55].…”
Section: Humanistic Burdenmentioning
confidence: 66%
“…The reliability of the questionnaire is related to the power of the survey application to give similar results if it is repeated in the same ways. The questionnaire was applied again three weeks after the first application to determine the reliability [39].…”
Section: Discussionmentioning
confidence: 99%